2015
DOI: 10.1016/j.pvr.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the epidemiological burden of HPV-related anogenital cancers, precancerous lesions, and genital warts in women and men in Europe: Potential additional benefit of a nine-valent second generation HPV vaccine compared to first generation HPV vaccines

Abstract: IntroductionA second generation HPV vaccine has been developed for the prevention of anogenital cancers and precancerous lesions of the cervix, vulva, vagina, anus and of genital warts due to nine HPV types.We estimated the annual burden of these diseases attributable to the nine HPV types compared to HPV types from first generation vaccines in women and men in Europe.Material and methodsIncidence rates from the IARC database, cancer registries, the literature and Eurostat population data were used.The burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 25 publications
(45 reference statements)
4
109
0
1
Order By: Relevance
“…Data confirm that types 16, 18, 31, 33, 45, 52 and 58 are amongst those most frequently detected [13]. Therefore, the nine-valent vaccine is expected to provide coverage against the majority of high-risk HPV types with carcinogenic properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Data confirm that types 16, 18, 31, 33, 45, 52 and 58 are amongst those most frequently detected [13]. Therefore, the nine-valent vaccine is expected to provide coverage against the majority of high-risk HPV types with carcinogenic properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HPV 6, 11, 16, 18, 31, 33, 45, 52, and 58 are associated with 78% and 91% of CIN2 and CIN3 occurrences, respectively . In Europe, HPV 16 and 18 account for approximately 72.8% of all cervical cancers and 45.5% of high‐grade cervical dysplasia, whereas HPV genotypes targeted by the nonavalent vaccine account for 89% of cervical cancers and 82.3% of high‐grade cervical lesions . In Portugal, HPV 16 and 18 have been identified as accounting for 54.4% of CIN2, 62.9% of CIN3, and 77.4% of ICC based on CLEOPATRE II study data, and the present analysis demonstrated that HPV 6, 11, 16, 18, 31, 33, 45, 52, and 58 account for 89.3%, 97.1%, and 96.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…En Europa, 21 países han introducido la vacuna contra VPH; de estos, solo 7 países (Dinamarca, Italia, Luxemburgo, Portugal, Suiza, España y Reino Unido) han alcanzado una tasa de cobertura ≥ 80 % (16,103). Si esta es la contraproducente situación sanitaria relacionada con la vacunación en los países con altos ingresos, con estructuras socio-sanitarios sólidas, donde en la mayoría aún no se está logrando una cobertura del 100 % de mujeres vacunadas, qué se puede esperar de los países con limitaciones sanitarias como los PMBI (99,(103)(104)(105).…”
Section: Perspectivas Sobre Las Estrategias De Prevenciónunclassified